Utilizing long-term opportunistic sightings records to document spatio-temporal shifts in mysticete presence and use in the Central Salish Sea - Olson, J. K.; Larson, S. E.; Robertson, F. C.; Miller, H.; Morrigan, A.; Berta, S.; Calambokidis, J. (Frontiers in Conservation Science, 2024)
The Salish Sea supports several baleen whale species, including humpback (Megaptera novaeangliae), gray (Eschrichtius robustus) and minke whales (Balaenoptera acutorostrata).With the exception of minke whales, these species were decimated by commercial whaling in the 1900s. Because recovery of these populations is monitored on broad spatial scales determined by distinct stocks/populations, their use of the Salish Sea ecosystem is not well documented or understood. We collated 17,436 opportunistic sighting reports to assess patterns in mysticete presence and distribution in the Salish Sea . We used the proportion of sightings for each species and spatial models targeting comparisons between species to limit the influence of spatio-temporal variation in reporting efforts. Humpback whale sightings have increased dramatically since the late 2000s, mirroring population-wide increases and suggesting a renewed use of historically important feeding areas. Gray whale sightings increased most notably at two distinct times (1989, 2017), both of which align with periods of high mortality experienced by the delisted Eastern North Pacific stock of gray whales and may reflect individuals straying from their migration routes. Sightings of minke whales remained relatively stable over this study period and were likely driven by a group of 30-40 individuals that forage off shallow banks and bathymetrically complex habitats around the San Juan Archipelago. Though it can be difficult to separate the bias that accompanies public sightings databases, citizen science efforts are